Re-thinking cell cycle regulators: the cross-talk with metabolism - Fajas, Lluis (Frontiers in Oncology, 2013)
Analyses of genetically engineered mice deficient for cell cycle regulators, including E2F1, cdk4, or, pRB showed that the major phenotypes are metabolic perturbations. These key cell cycle regulators contribute to lipid synthesis, glucose production, insulin secretion, and glycolytic metabolism and it has been shown how deregulation of those pathways can lead to metabolic perturbations and related metabolic diseases, such as obesity and type II diabetes. The cyclin-cdk-Rb-E2F1 pathway regulates adipogenesis in addition to its well-described roles in cell cycle regulation and cancer. It was also proved that E2F1 directly participates in the regulation of pancreatic growth and function. Similarly, cyclin D3, cdk4, and cdk9 are also adipogenic factors with strong effects on whole organism metabolism. These examples illustrate the growing notion that cell cycle regulatory proteins can also modulate metabolic processes. Cell cycle regulators are activated by insulin and glucose, even in non-proliferating cells. Most importantly cell cycle regulators trigger the adaptive metabolic switch that normal and cancer cells require in order to proliferate. These changes include increased lipid synthesis, decreased oxidative, and increased glycolytic metabolism. In summary, cell cycle regulators are essential in the control of anabolic, biosynthetic processes, and block at the same time oxidative and catabolic pathways, which are the metabolic hallmarks of cancer.